Relationship between nitrogen isotope ratios of NO3−and N2O in vertical porewater profiles through a polluted rain-fed peat bog. (August 2018) - Novak, Martin; Suarez, Silvia Parra; Gebauer, Gerhard; Thoma, Michael; Buzek, Frantisek; Cejkova, Bohuslava; Jackova, Ivana; Stepanova, Marketa; Prechova, Eva; Curik, Jan; Veselovsky, Frantisek; Valkova, Ivana; et al.
Abstract: We report a combination of δ 15 N-NO3 - and δ 15 N-N2 O values along vertical porewater profiles through a Sphagnum -dominated, high-elevation peat bog. Our objective was to distinguish between N2 O production from NO3 − via denitrification and N2 O consumption via reduction to N2 . Nitrate-N in runoff was isotopically heavier than NO3 − -N in atmospheric deposition, indicating export of organically-cycled N. Constant N2 O concentrations in porewater profiles contrasted with a shift toward higher δ 15 N-N2 O values upward. In the 60-30 cm depth interval, a significant negative correlation between δ 15 N-NO3 - and δ 15 N-N2 O values was observed. Higher δ 15 N values of residual NO3 − in the deepest peat layer reflected higher rates of NO3 − reduction. Isotopically heavier N2 O-N at shallower depths corresponded to residual N2 O following partial reduction to N2 . Highlights: There was a negative correlation between δ 15 N-NO3 - and δ 15 N-N2 O in peat pore water. Isotopically heavier NO3 − -N downcore resulted from higher N2 O production. Isotopically heavier N2 O-N upcore resulted from higher N2 O reduction to N2 . Microbial consumption of N2 O in saturated peat led to a loss of warming potential.